The antidepressant effect of short- and long-term zinc exposition is partly mediated by P2X7 receptors in male mice - Iring-Varga, Bernadett; Baranyi, Mária; Gölöncsér, Flóra; Tod, Pál; Sperlágh, Beáta (Frontiers in Pharmacology, 2023)
BACKGROUND: As a member of the purinergic receptor family, divalent cation-regulated ionotropic P2X7 (P2rx7) plays a role in the pathophysiology of psychiatric disorders. This study aimed to investigate whether the effects of acute zinc administration and long-term zinc deprivation on depression-like behaviors in mice are mediated by P2X7 receptors. METHODS: The antidepressant-like effect of excess zinc was studied using a single acute intraperitoneal injection in C57BL6/J wild-type and P2rx7 gene deficient (P2rx7 -/-) young adult and elderly animals in the Tail Suspension Test (TST) and the Forced Swim Test (FST). In the long-term experiments, depression-like behavior caused by zinc deficiency was investigated with the continuous administration of zinc-reduced and control diets for eight weeks, followed by the same behavioral tests. The actual change in zinc levels owing to the treatments was examined assaying serum zinc levels. Changes in monoamine and brain-derived neurotrophic factor (BDNF) levels were measured from the hippocampus and prefrontal cortex brain areas by enzyme-linked immunosorbent assay and high-performance liquid chromatography, respectively. RESULTS: A single acute zinc treatment, which elevated serum zinc level evoked antidepressant-like effect in both genotypes and age groups, except TST in elderly P2rx7 -/- animals, where no significant effect was detected. Likewise, the pro-depressant effect of zinc deprivation was observed in young adult mice in FST and TST, which was alleviated in case of the TST in the absence of functional P2X7 receptors. Among elderly mice no pro-depressant effect was observed in P2rx7 -/- mice in either test. Treatment and genotypice changes in monoamine and BDNF levels were also detected in the hippocampi. CONCLUSIONS: Changes in zinc intake were associated with age-related changes in behavior in the TST and FST. The antidepressant-like effect of zinc is partially mediated by the P2X7 receptor.